GONE FISHIN’ EFFECTS ON THE BUCHAREST STOCK EXCHANGE - RAMONA DUMITRIU; RAZVAN STEFANESCU (Annals of the University of Petrosani: Economics)
This paper investigates the presence of Gone Fishin’ Effects on the Romanian Capital Market from January 2000 to July 2013. In this analysis we employ daily values of five main indexes of Bucharest Stock Exchange. We use GARCH models to reveal this seasonality not only on indexes returns but also on the capital market volatility. In order to identify the differences between quiet and turbulent periods of time we split our sample of data into two sub-samples. The first, from January 2000 to December 2006, corresponds to a relative quiet period, while the second, from January 2007 to August 2013, corresponds to a turbulent period. Our results indicate the decline of Gone Fishin’ Effects on returns from the first to the second sub-sample.